Isolated Echogenic Intracardiac Foci: A Comparison of Aneuploidy Screening Tests [28P]. (May 2018) - Hacker, Francis; Griffin, Emily E.; Shaffer, Brian L.; Caughey, Aaron B.
Abstract : INTRODUCTION: The 2014 Fetal Imaging Workshop endorses obtaining a quad screen or cell-free fetal DNA (cfDNA) test in fetuses identified to have an isolated echogenic intracardiac foci (EIF) without prior aneuploidy screening. Our goal was to compare estimated outcomes and costs of the recommendation. We additionally hoped to gain information to assist providers in offering patient specific recommendations. METHODS: A decision-analytic model was constructed using TreeAge software and probabilities derived from the literature. The model compared use of quad testing to cfDNA in women with an isolated EIF identified on screening ultrasound, with T21 sensitivities assumed at 81% and 99% respectively. Baseline risk of T21 was assumed at 1/400. Positive likelihood ratio for T21 with an isolated EIF, was assumed to be 1.5. Outcomes of interest included T21 diagnosis, procedure related loss, termination, spontaneous abortion, and T21 live births. Strategies were compared to generate an incremental cost-effectiveness ratio, with a $100, 000/QALY threshold, and applied to a theoretical cohort of 100, 000. RESULTS: When compared to aneuploidy screening using quad testing, the strategy that utilized cfDNA after detection of an isolated EIF resulted in 47 fewer live T21 births and 85 additional QALYs with cost savings of $525, 964 per 100, 000 pregnancies; a dominant strategy in cost-effectiveness analysis. CONCLUSION: In a population with an isolated EIF identified on screening US without prior aneuploidy screening it is cost effective to offer cfDNA as compared to a quad screening test. Despite the higher cost of cfDNA, these results likely stem from the increased sensitivity and decreased false positive rate.